Enhancing Service Innovation: A Strategic Framework for Improved Healthcare Delivery - Willie, Michael Mncedisi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: To develop a strategic framework that enhances service innovation within South African medical schemes by examining micro- and macro-level factors influencing innovation capacity and competitiveness, addressing the need for accessible and affordable healthcare. Research Design and Methodology: A literature review guided by Willie’s Service Innovation Enabler (WSIE) framework was conducted, drawing on peer-reviewed articles, policy documents, and case studies relevant to South Africa’s healthcare system, focusing on digital transformation and regulatory trends. Findings and Discussion: Key enablers included leadership support, favorable regulation, and scheme size. Smaller schemes leveraged technologies like telemedicine effectively. COVID-19 accelerated digital adoption, though regulatory complexity and organizational resistance often impeded innovation efforts. Implications: Leadership-driven innovation strategies, supported by digital tools, are essential for improving service delivery. Supportive policy environments and further research are needed to assess long-term impacts on patient outcomes while addressing internal barriers to change within medical schemes.